2019
DOI: 10.3171/2019.5.peds1912
|View full text |Cite
|
Sign up to set email alerts
|

Association between postoperative DTI metrics and neurological deficits after posterior fossa tumor resection in children

Abstract: OBJECTIVEResection of posterior fossa tumors in children may be associated with persistent neurological deficits. It is unclear if these neurological deficits are associated with persistent structural damage to the cerebellar pathways. The purpose of this research was to define longitudinal changes in diffusion tensor imaging (DTI) metrics in white matter cerebellar tracts and the clinical correlates of these metrics in children undergoing resection of posterior fossa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Reports in healthy children 9 and adults 44 indicate no differences in FA or other diffusion MRI metrics between left and right DRTC tracts. However, many of the aforementioned studies have drawn different conclusions as to the required laterality of SCP damage in CMS; be it left 15 – which our results are in agreement with – right 19 , or bilateral 12,14,36,37,45 . These differences may be due in part to the small sample sizes seen in many of these reports, and collaborative multi-centre approaches to tackle this problem may provide more definitive answers.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Reports in healthy children 9 and adults 44 indicate no differences in FA or other diffusion MRI metrics between left and right DRTC tracts. However, many of the aforementioned studies have drawn different conclusions as to the required laterality of SCP damage in CMS; be it left 15 – which our results are in agreement with – right 19 , or bilateral 12,14,36,37,45 . These differences may be due in part to the small sample sizes seen in many of these reports, and collaborative multi-centre approaches to tackle this problem may provide more definitive answers.…”
Section: Discussionsupporting
confidence: 67%
“…A longitudinal study at three timepoints (pre-op, post-op and 1 year follow-up) showed statistically significant post-operative reductions in FA of both SCPs which persisted up to 1 year 14 . A similarly designed study showed post-operative reductions in FA in the left SCP only, and these changes were persistent in patients with ongoing ataxia at delayed follow-up imaging, but not in those with ongoing symptoms of mutism 15 . Neither of the latter two studies demonstrated pre-operative changes in FA at the SCP in patients who went on to develop CMS 14 15 ,.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Additionally, we neither performed a dedicated analysis of brain magnetic resonance imaging nor are tractography data available, thus limiting insight into additional factors leading to postsurgical dysphagia beside from surgical intervention. Future studies, including techniques like, e.g., diffusion tensor imaging (DTI), are warranted to address this issue in order to fully understand the nature of dysphagia following posterior fossa surgery [25][26][27].…”
Section: Discussionmentioning
confidence: 99%